IKLIM ORGANISASI, KUALITAS KEHIDUPAN KERJA DAN TURNOVER INTENTION PADA KARYAWAN PT.PAL INDONESIA (PERSERO) SURABAYA - Muh. Alfaridzi Reza Mahendra; Gartinia Nurcholis; Lutfi Arya (Fakultas Psikologi Universitas Hang Tuah, 2022)
The purpose of this study was to determine the existence of: The effect of organizational climate on turnover intention at PT. PAL Indonesia (Persero) Surabaya, influence of kualitas kehidupan kerja on turnover intention at PT. PAL Indonesia (Persero) Surabaya, the effect of organizational climate and kualitas kehidupan kerja together on turnover intention at PT. PAL Indonesia (Persero) Surabaya. This study uses a quantitative approach with survey method data and uses multiple regression analysis techniques. Data collection uses a turnover intention scale, an organizational climate scale, and a kualitas kehidupan kerja scale. The number of subjects in this study were 75 employees of the general engineering division of PT. PAL Indonesia (Persero) Surabaya. The sampling technique in this study used accidental sampling. The first minor hypothesis was accepted. The second minor hypothesis was accepted, proves that the organizational climate and kualitas kehidupan kerja affect turnover intention at PT. PAL Indonesia (Persero) Surabaya. The results showed that the level of turnover intention owned by employees of PT. PAL Indonesia (Persero) Surabaya was in the medium category.